Team-Based Collaboration in Higher Education Learning and Teaching A Review of the Literature - Newell, Catherine (SpringerBriefs in Education,, 2018)
This book examines what collaboration means in practice, and the factors that enable effective team collaboration for learning and teaching in higher education. It explains how academics can work more collaboratively, and how universities can organise and govern themselves by means of collaboration. The book brings together current research and commentaries on collaboration in higher education to provide important guidance derived from a synthesis and evaluation of the existing empirical research and commentaries in the field. The book will benefit all readers who are interested in making their own teams and higher education organisations more collaborative. It will help them plan collaborative innovations in their organisations, identify priorities for professional capacity building, and design collaborative organisational structures.